Hierarchical Kinematic Modelling and Optimal Design of a Novel Hexapod Robot with Integrated Limb Mechanism. (10th September 2015) - Xin, Guiyang; Deng, Hua; Zhong, Guoliang; Wang, Hengsheng
This paper presents a novel hexapod robot, hereafter named PH-Robot, with three degrees of freedom (3-DOF) parallel leg mechanisms based on the concept of an integrated limb mechanism (ILM) for the integration of legged locomotion and arm manipulation. The kinematic model plays an important role in the parametric optimal design and motion planning of robots. However, models of parallel mechanisms are often difficult to obtain because of the implicit relationship between the motions of actuated joints and the motion of a moving platform. In order to derive the kinematic equations of the proposed hexapod robot, an extended hierarchical kinematic modelling method is proposed. According to the kinematic model, the geometrical parameters of the leg are optimized utilizing a comprehensive objective function that considers both dexterity and payload. PH-Robot has distinct advantages in accuracy and load ability over a robot with serial leg mechanisms through the former's comparison of performance indices. The reachable workspace of the leg verifies its ability to walk and manipulate. The results of the trajectory tracking experiment demonstrate the correctness of the kinematic model of the hexapod robot.